Sustainability and eco – efficiency: a regional business model with a global vision (Colombia) - Melo Zamora, Marlén Deyanira; Zarta Campos, Mónica Alexandra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research arises as part of the analysis for the creation of eco-efficiency policies in companies and its purpose is to know the good environmental practices applied by companies in the service sector in the city of Girardot. It is presented as a descriptive - analytical study with a qualitative approach, using as an instrument the observation sheet applied to a sample of 30 service sector companies. Among the results obtained is the qualification according to a score between 0.0 and 1.0 and the analysis of the total result with weighting from 0% to 100% to 11 criteria evaluated.